2010
DOI: 10.1007/s13199-010-0050-x
|View full text |Cite
|
Sign up to set email alerts
|

A first report on the shrimp Pontonia sp. and other potential symbionts in the mantle cavity of the penshell Pinna carnea in the Dominican Republic

Abstract: Examination of the mantle cavity of 310 penshells Pinna carnea, collected from seagrass beds in southwestern Dominican Republic, revealed the presence of four species from three phyla as potential symbionts. The shrimp Pontonia sp. was found in 178 penshells, the cardinalfish Astrapogon stellatus in 18, an anemone (order Actiniaria) in two, and a pea crab (family Pinnotheridae) in one. The penshell likely provides these organisms with a refuge from predators. It also provides nutrition for shrimp as they consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…In socially monogamous symbiotic crustaceans, the population distribution also differs from a random Poisson distribution and host individuals harbor male-female pairs of symbiotic crustaceans either invariably [56] or with a frequency much greater than expected by chance alone [15,26,31,57]. Furthermore, there is often a tight correlation between the body size of male and female symbiotic individuals living in pairs and the body size of symbiotic individuals is tightly correlated with that of the host individuals harboring them [13,15,26,31].…”
Section: Discussionmentioning
confidence: 99%
“…In socially monogamous symbiotic crustaceans, the population distribution also differs from a random Poisson distribution and host individuals harbor male-female pairs of symbiotic crustaceans either invariably [56] or with a frequency much greater than expected by chance alone [15,26,31,57]. Furthermore, there is often a tight correlation between the body size of male and female symbiotic individuals living in pairs and the body size of symbiotic individuals is tightly correlated with that of the host individuals harboring them [13,15,26,31].…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to that reported for other socially monogamous crustaceans in which, (heterosexual) pairs are found in host individuals more frequently than expected by chance alone (e.g., Pontonia margarita : [ 11 ]; Pontonia sp . : [ 56 ]; Pontonia mexicana : [ 12 ]). Below, we discuss additional characteristics of the association between O .…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, in agreement to that reported for other socially monogamous shrimps (e.g., Pontonia margarita : [ 11 ]; Pontonia sp . : [ 56 ]), males of O . katoi were, on average, smaller than females, and the major cheliped of males did not exhibit positive allometry.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kennedy et al (2001) and Rada and Milat (2009) concluded that the association between Pontonia pinnophylax (Otto, 1821) and Pinna nobilis Linnaeus, 1758 represents commensalism, while Pacheco et al (2014) described a mutualistic relationship between the same shrimp species and the bivalve P. rudis Linnaeus, 1758. Symbiosis has been reported between several species of pontoniids and a wide range of host taxa including corals, jellyfish, sponges, and mollusks (Criales 1984, Morrison et al 2004, Baeza 2008, Baeza and Díaz-Valdés 2011, Baeza et al 2015. Bivalve hosts inhabited by small shrimp are one of the most studied models of symbiosis (Baeza 2008, Aucoin and Himmelman 2010, Baeza et al 2013. The morphological, sexual, and reproductive traits of decapods (Richardson et al 1997, Baeza 2008 in relation to host size (Baeza et al 2015) are important indicators used to infer the degree of symbiotic association between two species.…”
Section: Introductionmentioning
confidence: 99%